Metabolic changes induced by oral glucose tests in horses and their diagnostic use - Julien Delarocque; Florian Frers; Karsten Feige; Korinna Huber; Klaus Jung; Tobias Warnken (Journal of Veterinary Internal Medicine, 2021)
Abstract Background Little is known about the implications of hyperinsulinemia on energy metabolism, and such knowledge might help understand the pathophysiology of insulin dysregulation. Objectives Describe differences in the metabolic response to an oral glucose test, depending on the magnitude of the insulin response. Animals Twelve Icelandic horses in various metabolic states. Methods Horses were subjected to 3 oral glucose tests (OGT; 0.5 g/kg body weight glucose). Basal, 120 and 180 minutes samples were analyzed using a combined liquid chromatography tandem mass spectrometry and flow injection analysis tandem mass spectrometry metabolomic assay. Insulin concentrations were measured using an ELISA. Analysis was performed using linear models and partial least‐squares regression. Results The kynurenine : tryptophan ratio increased over time during the OGT (adjusted P‐value = .001). A high insulin response was associated with lower arginine (adjusted P‐value = .02) and carnitine (adjusted P‐value = .03) concentrations. A predictive model using only baseline samples performed well with as few as 7 distinct metabolites (sensitivity, 86%; 95% confidence interval [CI], 81%‐90%; specificity, 88%; 95% CI, 84%‐92%). Conclusions and Clinical Importance Our results suggest induction of low‐grade inflammation during the OGT. Plasma arginine and carnitine concentrations were lower in horses with high insulin response and could constitute potential therapeutic targets. Development of screening tools to identify insulin‐dysregulated horses using only baseline blood sample appears promising.